3D printing of functional polymers for miniature machines. Issue 1 (21st January 2022) - Xia, Neng; Jin, Dongdong; Iacovacci, Veronica; Zhang, Li
Abstract: Miniature robots and actuators with micrometer or millimeter scale size can be driven by diverse power sources, e.g. chemical fuels, light, magnetic, and acoustic fields. These machines have the potential to access complex narrow spaces, execute medical tasks, perform environmental monitoring, and manipulate micro-objects. Recent advancements in 3D printing techniques have demonstrated great benefits in manufacturing small-scale structures such as customized design with programmable physical properties. Combining 3D printing methods, functional polymers, and active control strategies enables these miniature machines with diverse functionalities to broaden their potentials in medical applications. Herein, this review provides an overview of 3D printing techniques applicable for the fabrication of small-scale machines and printable functional materials, including shape-morphing materials, biomaterials, composite polymers, and self-healing polymers. Functions and applications of tiny robots and actuators fabricated by 3D printing and future perspectives toward small-scale intelligent machines are discussed.